Proceedings of the International Scientific Conference - Review, review (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2015)
Proceedings of the International Scientific Conference «Modern Problems of Mathematical Modeling and Computational Methods». – Rivne :EPD RSHU, 2015. – 229 p.